ARTIKEL POLIP HIDUNG DAN PENATALAKSANAAN - Hanifah Qollama Astrid; Putu Ristyaning Ayu Sangging; Rani Himayani (Medula, 2023)
Nasal polyps are long-stemmed protrusions of the nasal cavity and it is include pseudotumors, which are a chronic inflammatory disease of the mucous membranes of the nose and paranasal sinuses. Nasal secretions, nasal congestion, sneezing, impaired sense of smell, male gender, increasing age and asthma are symptoms and risk factors associated with nasal polyps. Nasal polyps are aggressive and often seems like other pathologies in the nasal and paranasal cavities. Chronic Rhinosinusitis with Nasal Polyposis (CRSwNP) is the most common condition that usually occurs, nasal polyps are a continuation of acute rhinosinusitis. The etiology is not known with certainty, there are several underlying things. Diagnosis of nasal polyps can be enforced by history of anamnesis and clinical manifestations felt by the patient. Careful anamnesis, precise and fast diagnosis can have an impact on good and ideal treatment and management for increase a quality of life a patients, evaluation and management of side effects from treatment must be continuously controlled. Intranasal corticosteroids such as budesonide, fluticasone propionate, and mometasone furoate have been shown to reduce polyp size.